2020
DOI: 10.1017/s1463423620000286
|View full text |Cite
|
Sign up to set email alerts
|

Individual parental conversations with non-birthing parents

Abstract: Aim: The aim of this study was to describe Child Health Service (CHS) nurses’ experiences with conducting individual parental conversations (IPCs) with non-birthing parents. Background: CHS nurses in Sweden mainly focus on monitoring a child’s physical and mental development and the mothers’ health in order to support their parenthood. The assignment of the CHS includes identifying dysfunctional social relationships in a family and strengthening responsive parenting. An imbalance arises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The fathers whose cultural background was not Swedish perceived the conversation as an opportunity to talk about their child's physical health and development but considered topics such as relationships and their own well‐being as private matters, not to be disclosed at the CHS. This is in line with the findings of Larsson et al (2020) about how nurses reported that individual conversations with fathers from other cultural backgrounds challenging and that they were not on the same page as the fathers as to the aim of the conversation. They felt that their questions were not always understood, and that the fathers did not find it natural to talk about their own health and well‐being.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fathers whose cultural background was not Swedish perceived the conversation as an opportunity to talk about their child's physical health and development but considered topics such as relationships and their own well‐being as private matters, not to be disclosed at the CHS. This is in line with the findings of Larsson et al (2020) about how nurses reported that individual conversations with fathers from other cultural backgrounds challenging and that they were not on the same page as the fathers as to the aim of the conversation. They felt that their questions were not always understood, and that the fathers did not find it natural to talk about their own health and well‐being.…”
Section: Discussionsupporting
confidence: 91%
“…A conversation guide with three focus areas was used: the parental role and changes in life associated with parenthood; the relationship with the child; the parent's own health and well‐being, including the partner relationship and managing the work–family balance. The guide used was similar to a later version now used nationally in Sweden (Larsson et al, 2020; Rikshandboken) and a visual map of the focus areas, inspired by agenda mapping in Motivational Interviewing, was designed to be shared with the fathers during the conversation. There was also time for the fathers to raise their own questions and reflections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reticena et al ( 23 ) described a variety of professional support dimensions, such as promoting the development of the parental role, creating a safe environment for their children's upbringing, and providing guidance in life as parents. Together, these results stress the importance of support for both parents, which is in line with previous research that highlights the value of individual parent communication with the non-birthing parent to support family health and the child's upbringing ( 39 ). When planning future interventions for expectant and new parents, both the form of professional support and the types of the actual professionals involved in the provision of this support need to be taken into consideration.…”
Section: Discussionsupporting
confidence: 89%
“…This, in turn, permitted conversations focused on both children's and parents' needs and situations, as well as involving both parents to promote equal parenting. New parents can be surprised by changes in their parental-couple relationships (Deave and Johnson, 2008), and professional support can strengthen parents' parenting ability (Bäckström et al, 2021;Larsson et al, 2020). Research has reported that home visits can promote healthy family functioning and positive parenting in early childhood (Minkovitz et al, 2016) and can especially support three-way relationships between mother and child, father and child, and mother and father, in addition to strengthening the role of each parent (Barboza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%